2021
DOI: 10.1136/bmj.n2438
|View full text |Cite
|
Sign up to set email alerts
|

Health risks of extreme heat

Abstract: Record breaking heat events, once rare, are now common. 1 An extra 475 million exposures to heatwaves (that is, one person experiencing three days or more of extreme heat) were observed globally in 2019 compared with 1986-2005. 2 Clear evidence links the intensity and frequency of heat extremes to human induced global warming, which also increases the probability of compound events such as concurrent heatwaves and droughts. 3 The implications are serious: extreme heat has a substantial impact on all 17 UN su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Khosla et al revealed that wearing lightweight, light‐colored, and loose‐fitting clothing can enhance effective body cooling. They specifically recommended the use of breathable materials like cotton or linen 87 . Augmenting this, investigations advocate for the use of hats and sunglasses for supplementary outdoor protection 88 .…”
Section: Coping Strategies—the Psychological Approachmentioning
confidence: 99%
“…Khosla et al revealed that wearing lightweight, light‐colored, and loose‐fitting clothing can enhance effective body cooling. They specifically recommended the use of breathable materials like cotton or linen 87 . Augmenting this, investigations advocate for the use of hats and sunglasses for supplementary outdoor protection 88 .…”
Section: Coping Strategies—the Psychological Approachmentioning
confidence: 99%
“…With the ongoing climate change, extreme weather conditions, like storms and heat waves, are becoming more common on a global scale [ 1 ]. Such periods of extreme heat pose a serious threat to all forms of farming and agriculture and thus to the aim of feeding an ever-growing population.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to extreme heat can have adverse effects on human health; for instance, the "heat stroke" is a consequence of extreme heat exposure. Exposure to extreme heat and high humidity can produce adverse health consequences such as cardiopulmonary problems in high-risk groups and can cause sleep disruption, which is associated with impaired cognitive performance [5]. In order to mitigate UHI and the effects it has on human health and energy consumption, it is necessary to possess tools to monitor the UHI effect.…”
Section: Introductionmentioning
confidence: 99%